Dental caries and its association with increasing water fluoride concentration in district Rudraprayag, Uttarakhand - Sharma, Nidhi; Saxena, Vartika; Naithani, Manisha (International Journal Of Community Medicine And Public Health, 2021)
Background: Evidence from scientific literature confirms both beneficial and detrimental effects of fluoride on human health with only a narrow range between intakes associated with these effects. The limits of this range have been controversial among researchers since the 1930s. Considering this, the World Health Organization (WHO) permissible limit of fluoride in India has been reduced from 1.5 to 1.0 mg/l in 1998. This study aimed to evaluate the association between increasing water fluoride levels and dental caries prevention on permanent teeth. Methods: This cross-sectional study involved 1400 children (aged 6–19 years). Caries experience and dental fluorosis were recorded using DMFT/deft and Dean’s index respectively. Also, fluoride concentration in drinking water was analyzed. Around 14.4% of children had dental caries with maximum frequency among 9-10 years of age. A significant negative correlation between caries experience and water fluoride level was found (p<0.05), with the lowest DMFT scores at the fluoride level of 0.61–2 mg/l and the highest at 0.0–0.3 mg/l. Whereas, high prevalence of dental fluorosis was observed above 0.7 mg/l. Results: The study revealed that the presence of 0.3-0.7 mg/l fluoride in drinking water reduces dental caries, without an objectionable rise in dental fluorosis. Conclusions: It can be suggested that fluoride has anticaries property but due to a ‘narrow therapeutic window’ of 0.3-0.7 mg/l, in a country like India where endemic fluorosis is prevalent, its topical application should be encouraged which is almost equally effective with less systemic adverse effects.